Polyamide composite fibers and textured yarns

The eccentric core-sheath type polyamide conjugate fiber, composed of two crystalline polyamides with controlled water absorption and heat shrinkage, addresses the issues of stretchability loss and crimping difficulties in existing polyamide fibers, resulting in fabrics with enhanced elasticity and crimpability.

JP7604891B2Active Publication Date: 2024-12-24TORAY INDUSTRIES INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020541616
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-31
Filing Date
2020-07-27
Publication Date
2024-12-24
Estimated Expiration
2040-07-27

AI Technical Summary

Technical Problem

Existing polyamide composite fibers and processed yarns face issues with loss of stretchability due to processing steps, difficulty in crimping during heat and humidity, and decreased shrinkage properties over time, leading to woven or knitted fabrics with poor elasticity.

Method used

The development of an eccentric core-sheath type polyamide conjugate fiber composed of two types of crystalline polyamides with specific water absorption and heat shrinkage properties, ensuring a water absorption rate of 5.0% or less and a heat shrinkage stress of 0.15 cN/dtex or more, which maintains crimpability and stretchability even under high tension.

Benefits of technology

The solution provides polyamide composite fibers and processed yarns that yield woven or knitted fabrics with excellent stretchability, maintaining crimpability and elasticity even under high tension during moist or dry heat treatments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604891000003
    Figure 0007604891000003
  • Figure 0007604891000004
    Figure 0007604891000004
  • Figure 0007604891000001
    Figure 0007604891000001
Patent Text Reader

Abstract

The present invention addresses the problem of providing a polyamide composite fiber obtained from a woven or knitted fabric having excellent stretchability or a finished yarn comprising the same. This polyamide composite fiber is an eccentric core-in-sheath type of polyamide composite fiber comprising two kinds of crystalline polyamide (A) and crystalline polyamide (B) differing in composition from each other, wherein the water absorptivity and thermal contraction stress of the polyamide composite fiber after being left to stand still for 72 hours in an environment in which the temperature is 30℃ and the relative humidity is 90 RH% are 5.0% or less and 0.15 cN / dtex or more, respectively.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an eccentric sheath-core composite fiber made of polyamide and a textured yarn made of the same. [Background technology]

[0002] Polyamide fibers have been widely used for clothing applications because they are softer and have a better touch than polyester fibers. Representative polyamide fibers for clothing, such as nylon 6 and nylon 66, are single-filament yarns made of a single polymer, and because the fibers themselves have almost no elasticity, they are false-twisted or otherwise imparted with elasticity and are used for elastic woven or knitted fabrics. However, it has been difficult to obtain woven or knitted fabrics with fully satisfactory elasticity by subjecting such single-filament yarns to false-twisting or other processing.

[0003] In view of this, methods have been proposed for obtaining stretchable woven or knitted fabrics by using elastic fibers, or for obtaining stretchable woven or knitted fabrics by combining two types of polymers with different properties to form composite fibers with latent crimping properties that develop crimping through heat treatment in a dyeing process, etc. (see Patent Document 1).Furthermore, composite fibers in which two types of polyamides with different viscosities are arranged in a side-by-side or eccentric core-sheath configuration have also been proposed as polyamide composite fibers with latent crimping properties (see Patent Document 2).

[0004] In addition, a composite fiber and a processed yarn have been proposed that are made into a highly heat-shrinkable polyamide composite fiber containing an amorphous polyamide, and that can exhibit crimping properties in the warp direction even when subjected to wet heat or dry heat treatment under conditions of high tension in the warp direction, by which the composite fiber and the processed yarn can shrink with a stress that exceeds the restraining force of the woven or knitted fabric (see Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 110523 [Patent Document 2] Japanese Patent Publication No. 2002-363827 [Patent Document 3] International Publication No. 2017 / 221713 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when the composite fiber described in Patent Document 1 is obtained from two types of polyamide with different properties, the stretchability is lost through processing steps such as refining and dyeing due to the unique swelling property of polyamide, and the product may not have sufficient stretch. The same is true for the polyamide composite fiber described in Patent Document 2.

[0007] Furthermore, even if the composite fiber made of such polyamide described in Patent Document 2 has excellent shrinkability in the state of raw yarn or processed yarn, wrinkles specific to polyamide fibers are likely to occur in the moist heat process of scouring or dyeing of woven or knitted fabrics, and wrinkles formed in the moist heat process are difficult to remove in the dry heat process of the heat setting process, so that processing while applying tension to the woven or knitted fabric in the moist heat process is necessary to maintain the quality of the woven or knitted fabric. Thus, the polyamide composite fiber described in Patent Document 2 has the problem that the application of tension to the woven or knitted fabric in the moist heat process does not fully express the shrinkage of the raw yarn or processed yarn, resulting in a woven or knitted fabric with poor stretchability.

[0008] In addition, in the highly heat-shrinkable polyamide conjugate fiber described in Patent Document 3, the amorphous polyamide polymer undergoes moisture absorption and crystallization over time, which may result in a deterioration in shrinkage properties over time, resulting in a woven or knitted fabric with low stretchability.

[0009] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has been made to solve the above problems, and an object of the present invention is to provide a polyamide composite fiber which can give a woven or knitted fabric having excellent stretchability, and a textured yarn made therefrom. [Means for solving the problem]

[0010] The polyamide conjugated fiber of the present invention is an eccentric core-sheath type polyamide conjugated fiber made of two types of crystalline polyamide (A) and crystalline polyamide (B) having different compositions, and the polyamide conjugated fiber has a water absorption of 5.0% or less and a heat shrinkage stress of 0.15 cN / dtex or more after being left to stand for 72 hours in an environment of a temperature of 30°C and a relative humidity of 90 RH%. According to a preferred embodiment of the polyamide conjugate fiber of the present invention, the rigid amorphous amount of the polyamide conjugate fiber is 40 to 60%, and the stretch elongation rate is 30% or more. According to a preferred embodiment of the polyamide composite fiber of the present invention, the crystalline polyamide (A) is nylon 6 or a copolymer thereof. According to a preferred embodiment of the polyamide composite fiber of the present invention, the crystalline polyamide (B) is nylon 610 or a copolymer thereof. According to a preferred embodiment of the polyamide composite fiber of the present invention, the crystalline polyamide (A) is a core component, and the crystalline polyamide (B) is a sheath component. In the present invention, a textured yarn made of the above-mentioned polyamide composite fiber is obtained. According to a preferred embodiment of the textured yarn of the present invention, the stretch elongation rate is 100% or more. Effect of the Invention

[0011] According to the present invention, it is possible to obtain a polyamide composite fiber and a textured yarn that can give a woven or knitted fabric with excellent stretchability.Furthermore, according to the present invention, it is possible to obtain a polyamide composite fiber and a textured yarn that can give a woven or knitted fabric with excellent stretchability by shrinking with a stress that exceeds the restraining force of the woven or knitted fabric and fully expressing crimping properties in the warp direction even when subjected to wet heat or dry heat under a high tension in the warp direction. [Brief description of the drawings]

[0012] [Figure 1]FIG. 1 is a model cross-sectional view illustrating a cross section of an eccentric sheath-core type polyamide conjugate fiber of the present invention. [Diagram 2] 2(A) to 2(C) are model cross-sectional views illustrating examples of cross sections of other eccentric sheath-core type polyamide conjugate fibers of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The polyamide composite fiber of the present invention and the textured yarn using the same will be described below. In this specification, "mass" is synonymous with "weight".

[0014] The polyamide conjugated fiber of the present invention is an eccentric core-sheath type polyamide conjugated fiber made of two types of crystalline polyamide (A) and crystalline polyamide (B) having different polymer compositions, and is characterized in that the polyamide conjugated fiber has a water absorption of 5.0% or less and a heat shrinkage stress of 0.15 cN / dtex or more after being left to stand for 72 hours in an environment at a temperature of 30°C and a relative humidity of 90 RH%.

[0015] The polyamide composite fiber of the present invention is an eccentric sheath-core type composite fiber, and is composed of two types of crystalline polyamide (A) and crystalline polyamide (B) having different polymer compositions. The eccentric sheath-core type polyamide composite fiber refers to a composite fiber in which two or more types of polyamide form an eccentric sheath-core structure.

[0016] The polyamide composite fiber of the present invention must have a composite cross section formed by bonding two kinds of crystalline polyamides, and the two kinds of crystalline polyamides having different polymer compositions are present in a bonded state without being substantially separated. In the present invention, it is preferable that the crystalline polyamide (A) is the core component, the crystalline polyamide (B) is the sheath component, and the crystalline polyamide (A) is covered with the crystalline polyamide (B) to be an eccentric core-sheath type.

[0017] Here, the term "eccentricity" as used herein refers to the fact that, in the cross section of the polyamide conjugate fiber, the position of the center of gravity of the core component is different from the center of the cross section of the conjugate fiber.

[0018] Fig. 1 is a model cross-sectional view illustrating the cross section of an eccentric sheath-core polyamide conjugate fiber of the present invention (hereinafter also referred to as "polyamide eccentric sheath-core conjugate fiber"). In Fig. 1, polyamide eccentric sheath-core conjugate fiber 10A is composed of a core component (crystalline polyamide (A)) 1 and a sheath component (crystalline polyamide (B)) 2, and the position of the center of gravity of the core component crystalline polyamide (A) is different from the center of the conjugate fiber cross section.

[0019] 2(A) to 2(C) are model cross-sectional views illustrating the cross-sections of other polyamide eccentric sheath-core conjugate fibers of the present invention. Fig. 2(A), Fig. 2(B) and Fig. 2(C) respectively show embodiments of polyamide eccentric sheath-core conjugate fibers 10B to 10C having different shapes and arrangements of the eccentric sheath-core core component (crystalline polyamide (A)) 1 and the sheath component (crystalline polyamide (B)) 2, and similarly to Fig. 1, the position of the center of gravity of the core component crystalline polyamide (A) is different from the center of the conjugate fiber cross-section.

[0020] In a preferred embodiment, the composite ratio of crystalline polyamide (A) to crystalline polyamide (B) is crystalline polyamide (A):crystalline polyamide (B) = 6:4 to 4:6 (mass ratio). By setting the mass ratio to be preferably 6:4 to 4:6 in this manner, the water absorption rate of the polyamide composite fiber of the present invention can be controlled to 5.0% or less, and the obtained woven or knitted fabric is provided with excellent stretchability.

[0021] The polyamide composite fiber of the present invention is composed of two kinds of crystalline polyamides having different polymer compositions. Crystalline polyamides are polyamides that form crystals and have a melting point, and are polymers in which so-called hydrocarbon groups are linked to the main chain via amide bonds. Specific examples of crystalline polyamides include polycapramide, polyhexamethylene adipamide, polyhexamethylene sebacamide, polytetramethylene adipamide, condensation polymerization type polyamides of 1,4-cyclohexanebis and linear aliphatic dicarboxylic acids, and copolymers or mixtures thereof. However, it is preferable to use homogeneous polyamides in terms of easy reproduction of a uniform system and stable functional expression.

[0022] Examples of the crystalline polyamide (A) include nylon 6, nylon 66, nylon 4, nylon 610, nylon 11, nylon 12, and copolymers mainly composed of these, and are different from the crystalline polyamide (B). The crystalline polyamide (A) may contain components other than lactam, aminocarboxylic acid, diamine, and dicarboxylic acid in its repeating structure, so long as the effects of the present invention are not impaired. However, from the standpoint of spinnability and strength, elastomers containing polyols in the repeating structure are excluded.

[0023] From the viewpoints of spinnability, strength and peel resistance, the crystalline polyamide (A) is preferably a polymer in which 90% or more of the repeating units are a single lactam, an aminocarboxylic acid or a combination of a diamine and a dicarboxylic acid, more preferably 95% or more of the repeating units. In a particularly preferred embodiment, such a component is nylon 6 or a copolymer thereof from the viewpoint of thermal stability.

[0024] The crystalline polyamide (B) is obtained, for example, by combining a dicarboxylic acid unit mainly composed of a sebacic acid unit with a diamine unit. Among these, nylon 610 and its copolymers are most preferably used, because they have stable polymerization properties, little yellowing of the crimped yarn, and good dyeability. Here, sebacic acid can be produced, for example, by refining castor oil seeds, and is considered to be a plant-derived raw material.

[0025] Examples of dicarboxylic acids constituting dicarboxylic acid units other than sebacic acid units include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, phthalic acid, isophthalic acid, and terephthalic acid, and these can be incorporated within a range that does not impair the effects of the present invention.

[0026] In addition, these dicarboxylic acids are also preferably plant-derived dicarboxylic acids. The copolymerization amount of the dicarboxylic acid units other than the sebacic acid units is preferably 0 to 40 mol %, more preferably 0 to 20 mol %, and further preferably 0 to 10 mol %, based on the total dicarboxylic acid units.

[0027] Diamines constituting the diamine unit include diamines having 2 or more carbon atoms, preferably diamines having 4 to 12 carbon atoms, and specific examples thereof include putrescine, 1,5-pentanediamine, hexamethylenediamine, trimethylenediamine, nonanediamine, methylpentanediamine, phenylenediamine, ethambutol, etc. Furthermore, it is preferable that these diamines are also plant-derived diamines.

[0028] In addition, if necessary, pigments, heat stabilizers, antioxidants, weather resistance agents, flame retardants, plasticizers, release agents, lubricants, foaming agents, antistatic agents, moldability improvers, reinforcing agents, and the like can be added and blended into the crystalline polyamide (A) and the crystalline polyamide (B).

[0029] The polyamide composite fiber of the present invention must have a water absorption rate of 5.0% or less after being left to stand for 72 hours in an environment of a temperature of 30°C and a relative humidity of 90RH% (temperature 30°C x relative humidity 90RH%). The water absorption rate here is a value measured in accordance with JIS L 1013. By keeping the water absorption rate at 5.0% or less when treated for 72 hours at a temperature of 30°C x relative humidity of 90RH%, the swelling of the polyamide fiber under moist heat conditions such as the refining process and the dyeing process is small, and the elongation of the woven or knitted fabric during these processes is small. This makes it possible to carry out processes such as the refining process and the dyeing process without applying excessive tension to the woven or knitted fabric. As a result, a woven or knitted fabric with excellent stretchability is obtained.

[0030] On the other hand, the higher the water absorption rate, the more polyamide fibers tend to swell when hydrated. If the water absorption rate exceeds 5.0%, wrinkles and grains are likely to occur during the scouring, relaxation and dyeing processes, and the stretchability decreases because the fibers are usually stretched during processing.

[0031] The water absorption rate is preferably 4% or less, and although the lower limit of the water absorption rate cannot be specified, it is practically about 1.0%.

[0032] The water absorption rate can be controlled by selecting the crystalline polyamide (A) and the crystalline polyamide (B) and by the core-sheath composite ratio.

[0033] The polyamide composite fiber of the present invention must have a heat shrinkage stress of 0.15 cN / dtex or more. The heat shrinkage stress referred to here is measured using a heat shrinkage stress measuring device (e.g., Kanebo Engineering Co., Ltd., Model "KE-2") by tying the fiber yarn to be measured into a loop with a circumference of 16 cm, applying an initial load of 1 / 30 g of the yarn fineness (decitex), and measuring from 40°C to 210°C at a heating rate of 100°C / min, and the peak value of the obtained heat stress curve is taken as the maximum heat stress (cN / dtex).

[0034] When the heat shrinkage stress is 0.15 cN / dtex or more, even if wet heat treatment or dry heat treatment is performed under high tension in the warp direction, the stress exceeds the fabric binding force and shrinks, so that sufficient crimping can be achieved in the warp direction, and a woven or knitted fabric with good stretchability can be obtained. If the heat shrinkage stress is less than 0.15 cN / dtex, sufficient crimping is not achieved in the wet heat process under high tension, resulting in a woven or knitted fabric with poor stretchability.

[0035] The heat shrinkage stress is preferably 0.20 cN / dtex or more, more preferably 0.25 cN / dtex or more. If the heat shrinkage stress is too high, the crossing points of the woven fabric tend to become clogged and the stretchability is impaired, so the upper limit of the heat shrinkage stress is preferably 0.50 cN / dtex. The heat shrinkage stress can be controlled by using a high viscosity polymer and further by controlling the rigid amorphous amount of the fiber under heat drawing conditions of a low spinning temperature, a low spinning speed and a high draw ratio.

[0036] In the polyamide composite fiber of the present invention, the amount of rigid amorphous is preferably 40 to 60%. Rigid amorphous refers to amorphous material whose amount is determined by the method described in the Examples section, and is in an intermediate state between crystal and mobile amorphous material (conventional completely amorphous material), where molecular motion is frozen even above the glass transition temperature (Tg), and the material becomes fluid at temperatures higher than Tg (for example, see Minoru Toki, "DSC (3) - Glass transition behavior of polymers -", ​​Sen-i Gakkaishi Journal (Sen-i to Kogyo), Vol. 65, No. 10 (2009)).

[0037] The rigid amorphous amount is expressed as "100%-crystallinity-mobile amorphous amount." In the present invention, the polyamide composite fiber contains a crystalline portion, a rigid amorphous portion, and a mobile amorphous portion. The heat shrinkage stress depends on the restraining force of the rigid amorphous chains when the fiber structure is formed and the shrinkage of the mobile amorphous chains that are developed when heat treatment is performed. By setting the rigid amorphous amount within the above range, it is possible to develop the heat shrinkage stress.

[0038] The amount of rigid amorphous can be controlled by spinning, and like the thermal shrinkage stress, the amount of rigid amorphous can be controlled by using a high viscosity polymer and designing the manufacturing method.

[0039] By making the rigid amorphous amount 40% or more, the binding force of the rigid amorphous chains is exerted, and the desired heat shrinkage stress can be obtained without impairing the shrinkage of the amorphous chains having mobility. Also, by making the rigid amorphous amount 60% or less, the binding force of the rigid amorphous chains is exerted, and the shrinkage force of the amorphous chains having mobility can be maintained, and the desired heat shrinkage stress can be obtained. The rigid amorphous amount is preferably 45 to 55%.

[0040] In a preferred embodiment of the polyamide composite fiber of the present invention, the stretching extension percentage is 30% or more. The stretching extension percentage is an index of the crimpability of the raw yarn, and a higher value indicates a higher ability to develop crimp.

[0041] In the polyamide composite fiber of the present invention, when the fiber is formed, shrinkage difference occurs due to the difference in orientation between the crystalline polyamide (A) and the crystalline polyamide (B), and shrinkage occurs. However, polyamide fibers are generally prone to wrinkles during the refining and dyeing process of woven and knitted fabrics, and processing is performed under high tension in the warp direction in order to maintain the quality of the woven and knitted fabrics, so this shrinkage difference may be reduced by the influence of external force (high tension). In order to maintain this shrinkage difference, the raw yarn has a certain thermal shrinkage stress, so that the shrinkage of the raw yarn can be maintained, and if the stretching extension rate is 30% or more, a woven or knitted fabric with better stretchability can be obtained. The stretching extension rate is more preferably 100 to 200%. The stretching extension rate is expressed by the shrinkage difference between the two components, the crystalline polyamide (A) and the crystalline polyamide (B), and the larger the shrinkage difference, the higher the stretching extension rate.

[0042] The polyamide conjugated fiber of the present invention preferably has a total yarn fineness of 20 to 120 dtex. In particular, when used for sportswear, down jackets, outerwear, and innerwear, the total yarn fineness is more preferably 30 to 90 dtex. Although the single fiber fineness of the polyamide conjugated fiber cannot be specified, it is usually used in the range of 1.0 to 5.0 dtex.

[0043] Next, the method for producing the polyamide composite fiber of the present invention by melt spinning will be described. In the crystalline polyamide used in the present invention, the relative viscosity of the crystalline polyamide (A) is preferably 3.1 to 3.8. The relative viscosity of the crystalline polyamide (B) is preferably 2.6 to 2.8. In a more preferred embodiment, the relative viscosity ratio (A / B) of the crystalline polyamide (A) to the crystalline polyamide (B) is 1.2 to 1.4.

[0044] By selecting a crystalline polyamide having a relative viscosity within this range, shrinkage difference occurs after heat treatment, and a three-dimensional spiral structure is formed, resulting in crimping. In addition, during the spinning process, the polyamide undergoes amorphous to crystalline transition due to the heat of melting. At this time, the crystalline polyamide (A) having a high relative viscosity has a high molecular binding force, and therefore undergoes a slower amorphous to crystalline transition speed than the crystalline polyamide (B) having a low relative viscosity. Therefore, if the polyamide is cooled during the amorphous to crystalline transition after extrusion from the spinneret, an intermediate rigid amorphous state is likely to be produced, increasing the amount of rigid amorphous in the composite fiber and improving the thermal shrinkage stress and stretch elongation rate.

[0045] The polyamide composite fiber of the present invention has a composite cross section formed by bonding two kinds of crystalline polyamides, and has an eccentric core-sheath structure in which the core component crystalline polyamide (A) is covered with the sheath component crystalline polyamide (B). In the case of a conventional side-by-side structure in which the crystalline polyamide (A) is not covered with the sheath component crystalline polyamide (B), the crystalline polyamides having the above-mentioned relative viscosity difference are melted to form a composite cross section in a spinning pack, and when discharged from the spinneret, the polymer flow resistance is different, and the difference in flow speed makes it easy for yarn bending to occur, resulting in poor operability. Therefore, in the production of crystalline polyamide (A) and crystalline polyamide (B) having a difference in melt viscosity, the eccentric core-sheath structure of the present invention can be adopted to stably produce them using normal equipment.

[0046] Next, the production method of the polyamide composite fiber of the present invention by melt spinning and composite spinning will be described.

[0047] First, a method for producing the polyamide composite fiber of the present invention by high speed direct melt spinning will be illustrated below. The crystalline polyamide (A) and the crystalline polyamide (B) are melted separately, metered and transported using a gear pump, and a composite flow is formed as it is so as to have a core-sheath structure in a normal manner, and discharged from a spinneret using an eccentric core-sheath type composite fiber spinneret so as to have a cross section as shown in FIG. 1. The discharged polyamide composite fiber thread is cooled to 30°C by blowing cooling air using a thread cooling device such as a chimney. Next, the cooled thread is oiled using an oiling device and converged, taken up by a take-up roller at 1500 to 4000 m / min, passed through the take-up roller and the stretching roller, and stretched at 1.5 to 3.0 times according to the ratio of the peripheral speed of the take-up roller and the stretching roller. Furthermore, the thread is heat-set by a stretching roller, and wound up on a package at a take-up speed of 3000 m / min or more.

[0048] Separately, a method for producing the polyamide composite fiber of the present invention by high speed direct melt spinning will now be illustrated. The crystalline polyamide (A) and the crystalline polyamide (B) are melted separately, metered and transported using a gear pump, and a composite flow is formed as it is to have a core-sheath structure in a normal manner, and discharged from a spinneret using an eccentric core-sheath type composite fiber spinneret so as to have a cross section as shown in FIG. 1. The discharged polyamide composite fiber thread is cooled to 30°C by blowing cooling air using a thread cooling device such as a chimney. Next, the cooled thread is oiled using an oiling device and converged, and taken up by a take-up roller at 3000 to 4500 m / min, passed through the take-up roller and the stretching roller, and slightly stretched at 1.0 to 1.2 times according to the ratio of the peripheral speed of the take-up roller and the stretching roller. Furthermore, the thread is wound up on a package at a take-up speed of 3000 m / min or more.

[0049] In particular, the spinning temperature is appropriately designed based on the melting point of the crystalline polyamide (A) having a high relative viscosity. When the spinning temperature is high, the crystalline portion increases and the rigid amorphous amount decreases, whereas when the spinning temperature is low, the mobile amorphous amount increases and the rigid amorphous amount decreases slightly. Therefore, the spinning temperature is preferably 35 to 70°C higher than the melting point of the crystalline polyamide (A), and more preferably 45 to 60°C higher. By appropriately setting the spinning temperature, the rigid amorphous amount of the polyamide conjugate fiber of the present invention can be controlled, and the desired heat shrinkage stress and stretch elongation can be obtained.

[0050] In addition, by appropriately designing the draft drawing (take-up speed), the rigid amorphous content of the polyamide conjugate fiber of the present invention is increased, and the heat shrinkage stress and the stretch elongation rate are improved. The take-up speed is preferably 1500 to 4000 m / min.

[0051] When obtaining a drawn yarn, the rigid amorphous amount of the polyamide composite fiber of the present invention is increased and the heat shrinkage stress is improved by hot drawing using a heated take-up roller. The draw ratio is preferably 1.5 to 3.0 times, more preferably 2.0 to 3.0 times. The hot drawing temperature is preferably 30 to 90°C, more preferably 40 to 60°C.

[0052] In addition, by using a heating roller instead of a stretching roller for heat setting, the heat shrinkage stress of the polyamide conjugate fiber of the present invention can be appropriately designed. The heat setting temperature is preferably 130 to 180°C.

[0053] In addition, it is also possible to perform entanglement using a known entanglement device in the process up to winding. If necessary, it is also possible to increase the number of entanglements by performing entanglement multiple times. Furthermore, it is also possible to additionally apply an oil agent just before winding.

[0054] The textured yarn made of the polyamide composite fiber of the present invention uses the eccentric core-sheath type polyamide composite fiber of the present invention in at least a part of the yarn. The manufacturing method of the yarn processing is not limited, but examples thereof include a blending method and a false twisting method. As the blending method, air blending, double twisting, composite false twisting, etc. can be applied, but air blending is preferably used because it is easy to control the blending and the manufacturing cost is low. As the false twisting method, it is preferable to apply false twist using a pin type, friction type, belt type, etc. depending on the fineness and the number of twists.

[0055] In a preferred embodiment, the processed yarn made of the polyamide composite fiber of the present invention has a stretching extension rate of 100% or more. By setting the stretching extension rate to 100% or more, sufficient crimping is achieved in combination with the crimping of the false twisted yarn, resulting in a woven or knitted fabric with excellent stretchability. The higher the stretching extension rate, the greater the crimping, but processing wrinkles are more likely to occur, and in order to suppress wrinkles, the fabric is produced under a condition of applying a higher tension in the warp direction, which tends to impair the stretchability of the woven or knitted fabric, so a stretching extension rate of 120 to 200% is a more preferred embodiment.

[0056] As described above, the textured yarn made of the polyamide conjugate fiber of the present invention preferably has a stretch extension rate of 100% or more. The stretchable woven or knitted fabric is at least partially made using the polyamide conjugate fiber or textured yarn of the present invention. According to the present invention, even when a high tension is applied in the warp direction in the wet heat process, sufficient crimp can be developed, and a woven or knitted fabric having excellent stretchability can be provided.

[0057] The stretchable woven or knitted fabric made of the polyamide composite fiber or textured yarn of the present invention can be woven or knitted according to known methods. The structure of the woven or knitted fabric is not limited.

[0058] In the case of woven fabrics, the weave may be any of plain weave, twill weave, satin weave, or variations of these, or a mixture of these, depending on the application. In order to make a woven fabric with a firm texture and a fluffy feel, plain weaves with many restraint points, ripstop weaves that combine plain weaves and stone weaves, or even nanaco weaves, are preferred.

[0059] In the case of knitted fabrics, the structure may be any of the following structures depending on the application: plain weave circular knit fabric, interlock weave, half weave warp knit fabric, satin weave, jacquard weave, or variations or mixed weaves of these structures; however, a half weave structure of single tricot knit fabric is preferred because the knitted fabric is thin, stable, and has excellent elongation.

[0060] The use of the woven or knitted fabric made of the polyamide conjugated fiber or textured yarn of the present invention is not limited, but is preferably used for clothing, more preferably for sportswear, casual wear, and women's and men's clothing, such as down jackets, windbreakers, golf wear, rainwear, etc. In particular, it can be suitably used for sportswear and down jackets. EXAMPLES

[0061] Next, the polyamide composite fiber and textured yarn of the present invention will be specifically described with reference to examples.

[0062] A. Melting point: Thermal analysis was performed using a TA Instruments Q1000, and data processing was performed using Universal Analysis 2000. Thermal analysis was performed under nitrogen flow (50 mL / min), with a temperature range of -50 to 300 °C, a heating rate of 10 °C / min, and a chip sample mass of approximately 5 g (calorific data was normalized by mass after measurement). The melting point was measured from the melting peak.

[0063] B. Relative Viscosity: 0.25 g of a polyamide chip sample was dissolved in 25 ml of 98% by mass sulfuric acid to give a concentration of 1 g / 100 ml, and the flow time (T1) was measured at 25°C using an Ostwald viscometer. Subsequently, the flow time (T2) of only the 98% by mass sulfuric acid was measured. The ratio of T1 to T2, i.e., T1 / T2, was determined as the relative viscosity of sulfuric acid.

[0064] C. Total fineness: The method conformed to JIS L1013. A fiber sample was wound 200 times using a measuring machine with a frame circumference of 1.125 m at a tension of 1 / 30 (g). The sample was dried at 105°C for 60 minutes, transferred to a desiccator, and allowed to cool for 30 minutes in an environment with a temperature of 20°C and a relative humidity of 55%. The mass of the skein was measured, and the mass per 10,000 m was calculated from the obtained value. The total fineness of the fiber yarn was calculated assuming an official moisture regain of 4.5%. The measurement was performed five times, and the average value was taken as the total fineness.

[0065] D. Heat shrinkage stress: Using a Kanebo Engineering KE-2 heat shrinkage stress measuring machine, a fiber sample was tied into a loop with a circumference of 16 cm, an initial load of 1 / 30 g of the total fineness of the yarn was applied, and the load was measured as the temperature was changed from 40°C to 210°C at a heating rate of 100°C / min. The peak value of the obtained heat stress curve was taken as the heat shrinkage stress.

[0066] E. Stretching and elongation rate: A fiber sample was reeled off, immersed in boiling water at 90°C for 20 minutes, and then air-dried. A load of 2 mg / d was applied for 30 seconds to measure length A, and then a load of 100 mg / d was applied for 30 seconds to measure length B. The stretch elongation was calculated using the following formula. Stretching and elongation rate (%)=[(BA) / B]×100

[0067] F. Rigid amorphous amount: The rigid amorphous amount was measured using a TA Instruments Q1000 as a measuring device. The difference (ΔHm-ΔHc) between the heat of fusion (ΔHm) and the heat of cold crystallization (ΔHc) obtained from differential scanning calorimetry (hereinafter abbreviated as DSC), the specific heat difference (ΔCp) obtained from temperature-modulated DSC measurement, and the theoretical value of a 100% crystalline (completely crystalline) polyamide and the theoretical value of a 100% amorphous (completely amorphous) polyamide were used. Here, ΔHm0 is the heat of fusion of a polyamide (completely crystalline). Also, ΔCp0 is the specific heat difference around the glass transition temperature (Tg) of a polyamide (completely amorphous). The degree of crystallinity (Xc) and the mobile amorphous amount (Xma) were calculated based on the following formulas (1) and (2). Furthermore, the rigid amorphous amount (Xra) was calculated based on the following formula (3). The rigid amorphous amount was calculated from the average value of two measurements. (1)Xc(%)=(ΔHm-ΔHc) / ΔHm0×100 (2) Xma(%) = ΔCp / ΔCp0 × 100 (3) Xra(%)=100-(Xc+Xma)

[0068] The measurement conditions for DSC and temperature modulated DSC are shown below. (DSC measurement) Measurement equipment: TA Instruments Q1000 Data processing: TA Instruments Universal Analysis 2000 Atmosphere: nitrogen flow (50mL / min) Sample size: approx. 10 mg Sample container: Aluminum standard container Temperature and heat calibration: High purity indium (Tm=156.61℃, ΔHm=28.71J / g) Temperature range: Approximately -50 to 300°C Heating rate: 10℃ / min. First heating process (first run) (Temperature modulated DSC measurement) Measurement equipment: TA Instruments Q1000 Data processing: TA Instruments Universal Analysis 2000 Atmosphere: nitrogen flow (50 mL / min) Sample size: approx. 5 mg Sample container: Aluminum standard container Temperature and heat calibration: High purity indium (Tm=156.61℃, ΔHm=28.71J / g) Temperature range: Approximately -50 to 210°C Heating rate: 2℃ / min

[0069] G. Strength and elongation: Fiber samples were measured using Orientec's "TENSILON" (registered trademark), UCT-100, under the constant-speed elongation conditions specified in JIS L1013 (chemical fiber filament yarn test method, 2010). Elongation was determined from the elongation at the point showing the maximum strength in the tensile strength-elongation curve. Strength was determined as the value obtained by dividing the maximum strength by the fineness. Measurements were performed 10 times, and the average values ​​were taken as strength and elongation.

[0070] H. Water absorption rate at 30℃ and 90% RH: In accordance with JIS-L-1013 (2010 edition), the mass was measured in an absolutely dry state and after leaving the sample to stand for 72 hours at a temperature of 30°C and a relative humidity of 90% RH, and the moisture content was then measured.

[0071] I. Fabric Evaluation: (a) Manufacturing of weft yarn Polycaprolactam (N6) (relative viscosity 2.70, melting point 222° C.) was used, and melt extruded at a temperature of 275° C. using a spinneret having 12 nozzle holes. After melt extrusion, the obtained yarn was cooled, oiled, entangled, and then taken up by a take-up roller at 2570 m / min, subsequently stretched 1.7 times and heat-set at a temperature of 155° C. to obtain a nylon 6 yarn of 70 dtex and 12 filaments at a take-up speed of 4000 m / min.

[0072] (b) Textile manufacturing The eccentric core-sheath type polyamide composite yarns obtained in Examples 4 to 11 and Comparative Examples 1 to 3 were used as warps (warp density 90 / 2.54 cm) and the nylon 6 yarn obtained in (a) above was used as wefts (weft density 90 / 2.54 cm) to weave plain weave fabrics (warp / composite fiber) (basis weight 40 g / cm 2 In addition, the eccentric core-sheath type polyamide composite false twist textured yarns obtained in Examples 1 to 3 were used as warps (warp density 90 / 2.54 cm) and the nylon 6 yarn obtained in (a) above was used as wefts (weft density 90 / 2.54 cm) to weave a plain weave fabric (warp / textured yarn) (basis weight 40 g / cm). 2 ). The obtained fabric was scoured at 80°C for 20 minutes, then adjusted to pH 4 using 1% Kayanol Yellow N5G owf and acetic acid, dyed at 100°C for 30 minutes, fixed at 80°C for 20 minutes, and finally heat-treated at 170°C for 30 seconds to improve the texture.

[0073] (c) Elongation rate (stretchability) of the fabric in the warp direction Using a tensile tester, the 50 mm wide × 300 mm woven fabric samples obtained in Examples 1 to 10 and Comparative Examples 1 to 4 were stretched to 14.7 N in the warp direction of the fabric at a gripping distance of 200 mm and a pulling speed of 200 mm / min using a tensile tester, and the stretch percentage was measured and rated into the following three levels: "A," "B," and "C." A stretch percentage of 15% or more was determined to have stretchability. A (Good): 20% or more B (Acceptable): 15% to less than 20% C (unacceptable): Less than 15%

[0074] [Example 1] As the crystalline polyamide (A), nylon 6 (N6) with a relative viscosity of 3.3 and a melting point of 222°C was used, and as the crystalline polyamide (B), nylon 610 (N610) with a relative viscosity of 2.7 and a melting point of 225°C was used. The crystalline polyamide (A) was used as the core component, and the crystalline polyamide (B) was used as the sheath component. Each was melted and extruded using an eccentric core-sheath type composite fiber spinneret (12 holes, round holes) at a composite ratio (mass ratio) of crystalline polyamide (A) to crystalline polyamide (B) = 5:5 (spinning temperature 270°C). The yarn discharged from the spinneret was cooled and solidified in a yarn cooling device, oiled with a water-containing oil agent in an oiling device, entangled in a fluid entangling nozzle device, taken up at 3700 m / min on a take-up roller (room temperature 25°C), stretched to 1.1 times between stretching rollers (room temperature 25°C), and then wound up on a package at a take-up speed of 4000 m / min. A polyamide bicomponent fiber yarn with 62 dtex and 12 filaments, a stretch elongation of 49%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.16 cN / dtex, and a rigid amorphous amount of 41% was obtained. The obtained polyamide composite fiber yarn was subjected to disk false twisting under the conditions of a 1.25 draw ratio at a heater temperature of 190°C and a twist rate (D / Y) of 1.95 to obtain a false twist textured yarn with a stretch elongation rate of 130%. The obtained false twist textured yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 1.

[0075] [Example 2] A polyamide conjugated fiber yarn having 62 dtex, 12 filaments, a stretch elongation of 53%, a water absorption of 3.8%, a heat shrinkage stress of 0.21 cN / dtex, and a rigid amorphous content of 46% was obtained in the same manner as in Example 1, except that nylon 6 (N6) having a relative viscosity of 3.6 and a melting point of 222°C was used as the crystalline polyamide (A). The obtained polyamide composite fiber yarn was subjected to disk false twisting in the same manner as in Example 1 to obtain a false twist textured yarn with a stretch elongation rate of 150%. The obtained false twist textured yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 1.

[0076] [Example 3] A polyamide conjugated fiber yarn having 62 dtex and 12 filaments, a stretch elongation of 67%, a water absorption of 3.6%, a heat shrinkage stress of 0.25 cN / dtex, and a rigid amorphous amount of 53% was obtained in the same manner as in Example 1, except that a copolymer of nylon 6 and nylon 66 (N6 / N66) having a relative viscosity of 3.6 and a melting point of 200°C was used as the crystalline polyamide (A). The obtained polyamide composite fiber yarn was subjected to disk false twisting in the same manner as in Example 1 to obtain a false twist textured yarn with a stretch elongation rate of 200%. A woven fabric was formed using the obtained false twist textured yarn as a warp yarn. The obtained woven fabric had better stretchability than Examples 1 and 2. The results are shown in Table 1.

[0077] [Table 1]

[0078] [Example 4] As the crystalline polyamide (A), a copolymer of nylon 6 and nylon 66 (N6 / N66) with a relative viscosity of 3.6 and a melting point of 200°C was used, and as the crystalline polyamide (B), nylon 610 (N610) with a relative viscosity of 2.7 and a melting point of 225°C was used. The crystalline polyamide (A) was used as the core component, and the crystalline polyamide (B) was used as the sheath component. Each was melted and extruded using an eccentric core-sheath type composite fiber spinneret (12 holes, round holes) at a composite ratio (mass ratio) of crystalline polyamide (A) to crystalline polyamide (B) = 5:5 (spinning temperature 270°C). The yarn discharged from the spinneret was cooled and solidified by a yarn cooling device, oiled with a water-free oil by an oiling device, and then entangled by a fluid entangling nozzle device. The yarn was then taken up at 1700 m / min on a slightly heated take-up roller (temperature 50°C), stretched 2.4 times between heated stretch rollers (heat set temperature: 150°C), and then wound up on a package at a take-up speed of 4000 m / min. A polyamide composite fiber yarn having 62 dtex and 12 filaments, a stretch elongation rate of 117%, a water absorption rate of 3.6%, a heat shrinkage stress of 0.29 cN / dtex, and a rigid amorphous amount of 55% was obtained. A woven fabric was formed using the obtained polyamide composite fiber yarn as a warp. The obtained woven fabric had better stretchability than that of Example 5. The results are shown in Table 2.

[0079] [Example 5] As the crystalline polyamide (A), nylon 6 (N6) with a relative viscosity of 3.3 and a melting point of 222°C was used, and as the crystalline polyamide (B), nylon 610 (N610) with a relative viscosity of 2.7 and a melting point of 225°C was used. The crystalline polyamide (A) was used as the core component, and the crystalline polyamide (B) was used as the sheath component. Each was melted and extruded using an eccentric core-sheath type composite fiber spinneret (12 holes, round holes) at a composite ratio of crystalline polyamide (A) to crystalline polyamide (B) = 5:5 (spinning temperature 270°C). The yarn discharged from the spinneret was cooled and solidified in a yarn cooling device, oiled with a water-free oil agent in an oiling device, and then entangled in a fluid entangling nozzle device. The yarn was then taken up at 1700 m / min with a slightly heated take-up roller (temperature 50°C), stretched 2.4 times between heated stretching rollers (heat set temperature: 150°C), and then wound up on a package at a take-up speed of 4000 m / min. A polyamide composite fiber yarn with 62 dtex and 12 filaments, a stretch elongation rate of 83%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.20 cN / dtex, and a rigid amorphous content of 46% was obtained. The obtained composite fiber yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0080] [Example 6] A polyamide composite fiber yarn having 62 dtex 12 filaments, a stretch elongation rate of 81%, a water absorption rate of 3.3%, a heat shrinkage stress of 0.18 cN / dtex, and a rigid amorphous content of 45% was obtained in the same manner as in Example 5, except that the composite ratio of crystalline polyamide (A) to crystalline polyamide (B) was crystalline polyamide (A):crystalline polyamide (B) = 4:6. The obtained polyamide composite fiber yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0081] [Example 7] A polyamide composite fiber yarn having 62 dtex 12 filaments, a stretch elongation rate of 87%, a water absorption rate of 4.3%, a heat shrinkage stress of 0.23 cN / dtex, and a rigid amorphous content of 47% was obtained in the same manner as in Example 5, except that the composite ratio of crystalline polyamide (A) to crystalline polyamide (B) was crystalline polyamide (A):crystalline polyamide (B) = 6:4. The obtained polyamide composite fiber yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0082] [Example 8] A polyamide conjugate fiber yarn having 62 dtex, 12 filaments, a stretch elongation rate of 103%, a water absorption rate of 4.1%, a heat shrinkage stress of 0.20 cN / dtex, and a rigid amorphous amount of 46% was obtained in the same manner as in Example 5, except that nylon 6 (N6) having a relative viscosity of 3.6 and a melting point of 222°C was used as the crystalline polyamide (A) and a copolymer of nylon 610 and nylon 510 (N610 / N510) having a relative viscosity of 2.7 and a melting point of 225°C was used as the crystalline polyamide (B). The obtained polyamide conjugate fiber yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had better stretchability than that of Example 5. The results are shown in Table 2.

[0083] [Example 9] A polyamide composite fiber yarn having 62 dtex 12 filaments, a stretch elongation rate of 82%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.18 cN / dtex, and a rigid amorphous amount of 43% was obtained in the same manner as in Example 5, except that the yarn was taken up at 2050 m / min with a slightly heated take-up roller (50°C) and stretched 2.0 times between heated stretch rollers (heat set temperature: 150°C). The obtained polyamide composite fiber yarn was used as a warp yarn to form a woven fabric. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0084] [Example 10] A polyamide conjugate fiber yarn having 62 dtex and 12 filaments, a stretch elongation rate of 82%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.18 cN / dtex, and a rigid amorphous content of 43% was obtained in the same manner as in Example 5, except that the spinning temperature was set to 280°C. A woven fabric was formed using the obtained polyamide conjugate fiber yarn as a warp. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0085] [Example 11] A polyamide conjugate fiber yarn having 62 dtex and 12 filaments, a stretch elongation rate of 95%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.22 cN / dtex, and a rigid amorphous content of 49% was obtained in the same manner as in Example 5, except that the spinning temperature was set to 260°C. A woven fabric was formed using the obtained polyamide conjugate fiber yarn as a warp. The obtained woven fabric had excellent stretchability. The results are shown in Table 2.

[0086] [Comparative Example 1] A polyamide composite yarn of 62 dtex and 12 filaments was obtained in the same manner as in Example 5, except that nylon 6 (N6) with a relative viscosity of 2.7 and a melting point of 222°C was used as the crystalline polyamide (A). The composite yarn of Comparative Example 1, which has almost no difference in relative viscosity, had a small shrinkage difference after heat treatment, a low contraction rate of 13%, a heat shrinkage stress of 0.13 cN / dtex, and a rigid amorphous amount of 39%, both of which were low values. The resulting polyamide composite fiber yarn was used as a warp yarn, and the resulting woven fabric had poor stretchability. The results are shown in Table 2.

[0087] [Comparative Example 2] A polyamide composite yarn of 62 dtex 12 filaments was obtained in the same manner as in Example 5, except that the composite ratio of polyamide (A) and polyamide (B) was polyamide (A):polyamide (B) = 7:3. The polyamide composite yarn of Comparative Example 2, in which the ratio of polyamide (A) with high water absorption was increased, had a high water absorption rate of 5.8%. The obtained polyamide composite fiber yarn was used as a warp yarn to form a woven fabric in the same manner as in Example 5, but wrinkles remained. As a result, a woven fabric with poor stretchability was obtained by increasing the tension in the warp direction to the extent that the wrinkles would not remain. The results are shown in Table 2.

[0088] [Comparative Example 3] A polyamide conjugated fiber thread of 62 dtex 12 filaments was obtained in the same manner as in Example 5, except that nylon 6 (N6) with a relative viscosity of 3.3 and a melting point of 222 ° C. was used as the crystalline polyamide (A), and nylon 6 (N6) with a relative viscosity of 2.7 and a melting point of 225 ° C. was used as the crystalline polyamide (B). The polyamide conjugated fiber thread of Comparative Example 3, which was produced using polyamides with high water absorption, had a high water absorption rate of 6.2%. The obtained polyamide conjugated fiber thread was used as a warp thread to form a woven fabric in the same manner as in Example 5, but wrinkles remained, so the fabric was processed with a higher tension in the warp direction to the extent that the wrinkles did not remain, resulting in a woven fabric with poor stretchability. The results are shown in Table 2.

[0089] [Comparative Example 4] A polyamide conjugate fiber yarn having 62 dtex and 12 filaments, a stretch elongation rate of 53%, a water absorption rate of 3.8%, a heat shrinkage stress of 0.13 cN / dtex, and a rigid amorphous content of 36% was obtained in the same manner as in Example 5, except that the spinning temperature was 300°C. A woven fabric was formed using the obtained polyamide conjugate fiber yarn as a warp. The obtained woven fabric had poor stretchability. The results are shown in Table 2.

[0090] [Table 2]

[0091] Although the present invention has been described in detail using specific embodiments, it is clear to those skilled in the art that various modifications and variations are possible without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-141540) filed on July 31, 2019, and is incorporated by reference in its entirety. [Explanation of symbols]

[0092] 1: Core component (crystalline polyamide (A)) 2: Sheath component (crystalline polyamide (B)) 10A-10D: Polyamide eccentric core-sheath type composite fiber

Claims

1. The polyamide conjugated fiber is an eccentric core-sheath type polyamide conjugated fiber made of two types of crystalline polyamide (A) and crystalline polyamide (B) having different compositions, the polyamide conjugated fiber having a water absorption rate of 5.0% or less, a rigid amorphous amount of 40 to 60%, and a heat shrinkage stress of 0.15 cN / dtex or more after being left to stand for 72 hours in an environment of a temperature of 30°C and a relative humidity of 90 RH%.

2. The polyamide conjugate fiber according to claim 1, wherein the stretch elongation of the polyamide conjugate fiber is 30% or more.

3. 3. The polyamide composite fiber according to claim 1, wherein the crystalline polyamide (A) is nylon 6 or a copolymer thereof.

4. The polyamide composite fiber according to any one of claims 1 to 3, wherein the crystalline polyamide (B) is nylon 610 or a copolymer thereof.

5. The polyamide composite fiber according to any one of claims 1 to 4, wherein the crystalline polyamide (A) is a core component and the crystalline polyamide (B) is a sheath component.

6. A textured yarn comprising the polyamide composite fiber according to any one of claims 1 to 5.

7. The textured yarn according to claim 6, having a stretch elongation rate of 100% or more.

Citation Information

Patent Citations

  • Torque free filament

    JP1985028514A

  • Conjugate monofilament and its production

    JP1998266020A

  • Latently crimpable polyamide yarn and its production

    JP2000290837A

  • Conjugate polyamide fiber

    JP2001159030A

  • Latent crimping polyamide yarn and method for producing the same

    JP2002363827A